(untitled) (Swiss Medical Weekly, 2014)
Adopted orphan nuclear receptors, such as peroxisome proliferator-activated receptors (PPARs) and liver X receptors (LXRs), have emerged as key regulators of inflammation and immunity and likewise control skeletal homeostasis. These properties render them attractive targets for the therapy of various inflammatory and autoimmune diseases affecting the musculoskeletal system. This review summarises the current knowledge on the role of these families of receptors during innate and adaptive immunity as well as during the control of bone turnover and discuss the potential use of targeting these molecules during the treatment of chronic diseases such as osteoarthritis, rheumatoid arthritis and osteoporosis.